PENENTUAN LOKASI ATM BANK SYARIAH INDONESIA DI WILAYAH JEMBER KOTA MENGGUNAKAN K-MEANS CLUSTERING - Nila Al Indiani; Kiswara Agung Santoso; Dian Anggraeni (UPT Penerbitan Universitas Jember, 2022)
All transactions are inseparable from the role of the ATM as a supporter the business entity financial improvement. Therefore, the existence of an ATM has now become a general need of modern society. Currently, the population of Jember Regency is 2,568.88 people, and 10 ATM have been established, which means the population ratio and the number of ATM are not balanced, so it is necessary to make a data grouping in order to obtain the location of the ATM establishment that can reach the surrounding villages. This research examined the K-Means Clustering method in the case of determining the location of an ATM based on the distance from the center of the crowd. Calculation of distance using Google Maps K-Means Clustering algorithm was used to group 40 data points for the center of each village into 6 clusters. This research assumed that the centroid is the location of the ATM establishment and the cluster members were the village that can be reached by the centroid. The results of C1-C6 grouping were Tanjung Market, Pakusari Market, MTSN 2 Jember, KUA Arjasa, SMPN 3 Arjasa, and SMAN 4 Jember, sequentially. Keywords: ATM Location, Euclid Distance, K-Means Clustering